DINAMIKA PENDIDIKAN ISLAM DI THAILAND - Nuruzzahri, Nuruzzahri (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2023)
The country of Thailand, also known as Muangthai, or Siam, or the land of the white elephant, is located in northern Malaysia, and is often depicted as a flower that blooms on a stalk. Thailand means an independent country, because it is the only country in Southeast Asia that has never been colonized by western powers or other countries in the world. The Muslim population of Thailand is mostly domiciled in the southern part of Thailand, which is an area that is often called Patani, such as in the provinces of Songkhla, Yala, Narathiwat, Setul and its surroundings which historically were part of Daulah Islamiyyah Pattani. In simple terms, Islamic education is education that is